Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Berpikir Kreatif Siswa Dalam Memecahkan Masalah Di Kelas Vi Sd Negeri 1 Glanggang Pakisaji - Maulida Adhiyah; Nur Ali; A. Nurul Kawakip (Publikasi Indonesia, 2025)
The ability to think creatively is the ability to find many possible answers to a problem, where the emphasis is on the quantity, appropriateness, and diversity of answers. Education must equip students with skills that can be used to overcome the problems faced by students. Understanding of self-ability must also be considered so that the characteristics of students' creative thinking ability in solving a problem can be clearly known. The use of problem-based learning can be the right learning model to improve students' creative thinking skills. This study aims to determine the influence of the problem-based learning (PBL) learning model on students' creative thinking ability in solving problems. This study is a quantitative research with a non-equivalent control group design. The research was conducted at SD Negeri 1 Glanggang Pakisaji with the subjects of class VI B as the control class and class VI A as the experimental class. The research instrument consists of teaching modules, creative thinking ability tests, and guidelines for assessing students' creative thinking ability in solving problems. Data analysis was carried out with the help of the SPSS 25 program. The results of the study show that (1) The PBL learning model has a positive and significant influence on students' creative thinking ability in solving problems. (2) There was a significant difference in students' creative thinking ability in solving problems in the experimental class and the control class as evidenced by the average N-Gain test of the control class was 15.77% (ineffective) while the average N-Gain test of the experimental class was 66.44% (quite effective). Students' creative thinking ability in solving problems in the control class was classified as medium (96.16), while in the experimental class it was classified as very high (140.16). (3) The PBL learning model is more effective in improving students' creative thinking skills in solving problems when compared to the conventional learning model. Problem-based-learning can be an alternative learning model to improve students' creative thinking skills in solving problems.